2020
DOI: 10.3390/ijms21061927
|View full text |Cite
|
Sign up to set email alerts
|

NEAT1 is Required for the Expression of the Liver Cancer Stem Cell Marker CD44

Abstract: CD44, a cancer stem cell (CSC) marker, is required for maintaining CSC properties in hepatocellular carcinoma (HCC). Nuclear enriched abundant transcript 1 (NEAT1), a long noncoding RNA (lncRNA), is an oncogenic driver in HCC. In the present study, we investigated the significance of the NEAT1 gene in association with CD44 expression in liver CSCs of human HCC cell lines. The CSC properties were evaluated by spheroid culture, CSC marker expression, and sensitivity to anti-cancer drugs. The expression of both N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 51 publications
2
32
0
Order By: Relevance
“…52,53 We recently elucidated that the knockout of the NEAT1 gene resulted in decreased CSC-like properties of HCC cell lines, which were concomitant with the abolishment of CD44 expression. 31 Rescue experiments supported the notion that CD44 expression in HCC was highly dependent on NEAT1 expression. As described above, since CD44 regulates CSCs, it was postulated that NEAT1 might maintain CSC-like properties via CD44.…”
Section: Lncrnamentioning
confidence: 67%
See 2 more Smart Citations
“…52,53 We recently elucidated that the knockout of the NEAT1 gene resulted in decreased CSC-like properties of HCC cell lines, which were concomitant with the abolishment of CD44 expression. 31 Rescue experiments supported the notion that CD44 expression in HCC was highly dependent on NEAT1 expression. As described above, since CD44 regulates CSCs, it was postulated that NEAT1 might maintain CSC-like properties via CD44.…”
Section: Lncrnamentioning
confidence: 67%
“…However, we found that NEAT1 overexpression restored the CSClike properties even in CD44-deficient HCC cells. 31 These findings suggested that NEAT1 maintained the CSC-like properties of HCC cell lines in both CD44independent and CD44-dependent manners.…”
Section: Lncrnamentioning
confidence: 87%
See 1 more Smart Citation
“…indicating that the ability of NEAT1_1 to maintain CSC properties is in a CD44-independent manner. 90 These studies suggest that NAET1…”
Section: Ta B L E 1 (Continued)mentioning
confidence: 95%
“…CD44 is encoded by a highly conserved gene, and its premessenger RNA could be alternatively spliced into mature mRNAs encoding variant isoforms (CD44v) or standard isoform (CD44s). CD44s have been reported to be tightly related to the poor prognosis of patients with HCC and contribute to tumor metastasis and chemoresistance [9][10][11][12] . Moreover, Bousoik et al 13 showed that shedding extracellular domain of CD44 reduced caspase-1/IL1B activation in macrophage, which suggesting CD44s might be an upstream regulator of caspase-1/IL1B.…”
Section: Introductionmentioning
confidence: 99%